The Psychology of Poverty: Current and Future Directions - Ho, Yuen; Park, Ye Rang; Hallez, Kristina; Kaur, Supreet; Zhao, Jiaying; Srinivasan, Mahesh (Current Directions in Psychological Science, 2025)
An emerging literature on “the psychology of poverty” suggests that the experience of poverty itself has psychological consequences, some of which may make escaping poverty more difficult. We synthesize the evidence base from both psychology and economics using an organizing framework comprising four sets of mechanisms: cognitive function, mental health, beliefs, and preferences. We discuss the strength of the evidence supporting both how poverty affects these four mechanisms and how these four mechanisms in turn affect poverty. As our review shows, the existing evidence has clearly established proof of concept that psychological factors exist in the experience of and response to poverty. However, there is still a lack of evidence on whether these effects are meaningful in magnitude and lead to the perpetuation of poverty. We conclude by summarizing promising future directions for research that could help close these evidence gaps, with important implications for the design of poverty reduction policies.
PUBLISHED
Keywords: psychology of poverty; cognitive function; mental health; beliefs; preferences; International Development; Development economics; Economics; Social Identity